In-Home Medication: Integrating Multidisciplinary Perspectives in Design-Driven Pharma Practices - Penati, Antonella Valeria (Research for Development, 2025)
This is an open access book. This book provides a distinctive perspective on the daily utilization and consumption of medicines and drugs. It seamlessly integrates the research traditions of the medical and pharmaceutical realms with the approach of fostering the relationship between users and products, a characteristic of design and user studies. By applying a diverse range of expertise, the authors endeavor to reestablish the interconnectedness of issues that place the drug and the indispensable information for its use directly into the hands of the patient. The primary objective is to formulate an initial set of recommendations and compile a repertoire of best practices. Consequently, this book becomes an indispensable resource for students, professionals, and academics engaged in design culture, as well as those operating within the healthcare domain, such as the pharmaceutical industry, medical practitioners, and pharmacists. It is equally valuable for individuals working in institutions responsible for regulating medicines and overseeing their presence in the market. As a comprehensive guide, this book serves as an essential read, offering insights that bridge the gap between various sectors involved in the intricate landscape of medicine and drug consumption.